Peer support and the mental health of Indonesian migrant workers: The mediating role of spiritual well-being and coping strategies - Ghufron, M. Nur; Azmi, Khilman Rofi'; Al-Giffari, Haekal Adha (Psikohumaniora: Jurnal Penelitian Psikologi, 2024)
Peer support has been highlighted as an important factor in the mental health of Indonesian migrant workers abroad. Although many studies have investigated spiritual well-being and coping strategies, few have investigated the role of these as mediating variables. This study aims to determine the direct and indirect influences of peer support on mental health through the spiritual well-being and coping strategies of Indonesian migrant workers living abroad. The research participants were 183 Indonesian migrant workers based overseas. The sampling technique employed was convenience sampling. The data collection technique used was a scale questionnaire, including the peer support scale, coping strategy scale, spiritual well-being scale and mental health scale. The technique for analyzing the data was structural equation modeling. The results show that peer support (β = .247, p < .01), spiritual well-being (β = .176, p < .01), and coping strategies (β = .514, p < .01) had a direct effect on mental health. At the same time, there was an indirect effect of peer support (β = .159, p < .01), which was mediated by spiritual well-being and coping strategies. The research has theoretical implications regarding the importance of the encouragement of friends for the mental health of Indonesian migrant workers, especially when reinforced with spiritual well-being and coping strategies.